Authorisation of Writing and Relationship to Student Interests in Arabic Language - Rahman, Siti Nur Hadis A; Nor, Noraniza Mohd; Zahar, Syakirah; Mohamad, Siti Norlina; 'Aqilah Mahpuz,, Asma Nurul; Mohd Roslan, Nor Razan Izzati (International Journal of Psychosocial Rehabilitation, 2020)
Arabic language learning at religious schools in Malaysia has been there for a long time. The aim of this study was to identify the level of written proficiency of students and to examine the relationship between student interest and Arabic writing skills. A total of 40 students of pure science were chosen as respondents using the objective sampling method. The methodology of this study is to use quantitative studies by distributing questionnaires and analysing them using the Statistical Package for the Social Science (SPSS) version 23.0. The results showed that students’ writing skills were at a moderate level. In the correlation analysis, r=.479 showed that there was a relationship between dependent variables and independent variables, but the relationship was weak. r = .479 means that the variance r2 value is .4792 = .23. These variance values indicate that 23% of students’ writing skills are due to their interest in Arabic language. This means that the value of variance can be used as an indication of the influence factors that cause changes in the effect of a relationship. However, 77% of other factors could not be detected. It may be due to student attitudes, crafts, motivation and other factors not reflected in this relationship.